Quality Planning Process Of Construction Contractors: Case Studies In Sri Lanka - Senaratne, Sepani; Jayarathna , Thushangi (Penerbit Universiti Sains Malaysia, 2012)
Within quality management efforts, modern organisations pay more attention to improving the quality planning process. However, construction contractors in developing countries such as in Sri Lanka still lag in their practice of effective quality planning. Thus, the key research question of this study was "how do Sri Lankan construction contractors approach quality planning?" Within this question, the study's primary objectives were to explore whether the Sri Lankan construction contractors practice quality planning effectively and the extent to which they are ready to implement strategic quality planning. The research method adopted for this study was qualitative and used three case studies representing three major contractors in Sri Lanka. The study revealed that ISO 9000 is the most popular quality management system practiced by Sri Lankan construction contractors. The contractors are not yet ready to implement strategic quality planning due to several barriers. Building on these case study findings, several prerequisites for the successful implementation of strategic quality planning are proposed that will be useful for contractors who operate in similar environments.